SOSIALISASI MITIGASI BENCANA KEBAKARAN DIKAMPUNG HARENDONG DESA SINDANGGALIH KARANGPAWITAN KABUPATEN GARUT - Desy Syswianti; Elang Mohamad Atoilah; Andhika Lungguh Perceka; Hasbi Taobah Ramdani; N. Ai Erlinawati; Herlin Rusyani; Aceng Ali Awaludin (LP4M STIKes Karsa Husada Garut, 2022)
Indonesia is a disaster-prone country, both natural and non-natural disasters as well as social disasters. The purpose of this service is to educate the public to be prepared for the arrival and impacts arising from disasters experienced by themselves or the community. The technique used in this community service is to socialize fire disaster mitigation and explore community knowledge about fire disaster mitigation so that a Community-Based Fire Disaster Mitigation Model poster is formed using a cooperative-participatory method in collaboration between the government and the community. The results obtained from the implementation of this activity were community knowledge from 40 people who took part in the socialization on disaster mitigation before participating in this activity 45% or 18 people who knew about disaster mitigation education, and after participating in the socialization as much as 90% or 36 people understood information on disaster mitigation. The overview obtained is that it is important for the community to know, understand and be able to apply the knowledge of fire disaster mitigation which is socialized to the Sindanggalih village community. Considering that the location of Sindanggalih Village is quite close to the city which is full of hills and mountains and there are still many trees, so that if a fire occurs, the community will certainly experience enormous difficulties because Sindanggalih Village does not yet have fire extinguisher facilities. So it becomes very important to socialize fire disaster mitigation for Sindanggalih villagers, in order to prevent the causes of fires at an early stage, including when a fire disaster occurs, how can residents already know and understand what actions must be taken in order to survive and successfully extinguish the fire.